STRATEGI DIGITAL MARKETING DAN PERENCANAAN KEUANGAN YANG EFEKTIF PADA UMKM DI KABUPATEN BOYOLALI - Nurita Elfani Prasetyaningrum; Ramadhian Agus Triono Sudalyo (JURNAL ILMIAH EDUNOMIKA, 2024)
This research explores and analyzes effective digital marketing strategies and financial planning for Micro, Small, and Medium Enterprises (UMKM) in Boyolali Regency. UMKM plays a vital role in the local economy, but often faces challenges in competing in the increasingly complex digital era. This study involves in-depth interviews with UMKM owners, market data analysis, and case studies to understand the extent to which UMKM in Boyolali Regency have utilized digital marketing, particularly in the use of social media, online advertising, and search engine optimization. We also evaluate financial planning practices that support business growth and sustainability. The results of this research provide practical guidance for UMKM owners and local stakeholders in developing digital marketing strategies that align with local market characteristics and leverage existing digital opportunities. This research also identifies financial planning practices that can help UMKM manage financial resources wisely. The implications of this research support the growth and sustainability of UMKM in Boyolali Regency and provide valuable insights in the context of UMKM at the national level. Keywords: digital marketing, financial planning, UMKM